Exome Sequencing of 5 Families with Severe Early-Onset Periodontitis. (February 2022) - Richter, G.M.; Wagner, G.; Reichenmiller, K.; Staufenbiel, I.; Martins, O.; Löscher, B.S.; Holtgrewe, M.; Jepsen, S.; Dommisch, H.; Schaefer, A.S.
Periodontitis is characterized by alveolar bone loss leading to tooth loss. A small proportion of patients develop severe periodontitis at the juvenile or adolescent age without exposure to the main risk factors of the disease. It is considered that these cases carry rare variants with large causal effects, but the specific variants are largely unknown. In this study, we performed exome sequencing of 5 families with children who developed stage IV, grade C, periodontitis between 3 and 18 y of age. In 1 family, we found compound heterozygous variants in the gene CTSC (p.R272H, p.G139R), 1 of which was previously identified in a family with prepubertal periodontitis. Subsequent targeted resequencing of the CTSC gene in 24 patients <25 y of age (stage IV, grade C) identified the known mutation p.I453V (odds ratio = 4.06, 95% CI = 1.6 to 10.3, P = 0.001), which was previously reported to increase the risk for adolescent periodontitis. An affected sibling of another family carried a homozygous deleterious mutation in the gene TUT7 (p.R560Q, CADD score >30 [Combined Annotation Dependent Depletion]), which is implicated in regulation of interleukin 6 expression. Two other affected siblings shared heterozygous deleterious mutations in the interacting genes PADI1 and FLG (both CADD = 36), which contribute to the integrity of the environment–tissue barrier interface. Additionally, we found predicted deleterious mutations in the periodontitis risk genes ABCA1, GLT6D1, and SIGLEC5 . We conclude that the CTSC variants p.R272H and p.I453V have different expressivity and diagnostic relevance for prepubertal and adolescent periodontitis, respectively. We propose additional causal variants for early-onset periodontitis, which also locate within genes that carry known susceptibility variants for common forms. However, the genetic architecture of juvenile periodontitis is complex and differs among the affected siblings of the sequenced families.